THE ETHICAL IMPLICATIONS OF REMOTE ROBOTIC SURGERY: WHO CONTROLS THE SCALPEL? - KAMALOVA NASIBA BAKHTIYOROVNA; B.A. Umarov (Ta'lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT   Remote robotic surgery has introduced groundbreaking advancements in modern healthcare,  allowing  expert  surgeons  to  operate  on  patients  from  thousands  of kilometers away.  While this innovation offers increased access to specialized care, especially in underserved regions, it also raises complex ethical questions. Who bears responsibility if a complication arises during a remote procedure? How is informed consent managed when the surgeon and patient have never met face-to-face? What safeguards are in place to prevent system failures or cyber interference? This paper explores  the  moral,  legal,  and  practical  implications  of  remote-controlled  surgical procedures,  focusing  on  accountability,  patient  autonomy,  data  privacy,  and  the evolving relationship between human judgment and machine precision in life-or-death situations.